Effect of Te doping on the thermopower of PbSe1–xTex. Issue 6 (1st December 2012) - Basu, Ranita; Aswal, D.K. D. K.; Bhatt, Ranu; Singh, Ajay; Bhattacharya, S.; Gupta, S.K. S. K.
Abstract : We have studied the effect of Te doping on structural, morphological and thermopower of PbSe for the composition PbSe1-x Tex (x= 0.0, 0.2, 0.50, 0.75, 0.9 and 1.0). The samples were prepared using melting and rocking method. The scanning electron microscopy indicated that all the samples have lamellar morphology. The x-ray diffraction analysis suggested that the lattice parameter increases linearly with dopant concentration (x). The temperature dependence of thermopower measured for samples having different x revealed unusual increase in thermopower for the composition x=0.5 e.g. at 427 °C, the thermopower values for PbSe0.5 Te0.5, PbTe and PbSe were respectively 292, 188 and 134 µV/K. A dramatic thermopower enhancement for PbSe0.5 Te0.5 is attributed to scattering of the majority charge carriers by the defect sites. The authors have studied the effect of Te doping on structural, morphological and thermopower of PbSe for the composition of PbSe1–x Tex (x = 0·0, 0·2, 0·50, 0·75, 0·9 and 1·0). The samples were prepared using melting and rocking. The scanning electron microscopy indicated that all the samples have lamellar morphology. The X-ray diffraction analysis suggested that the lattice parameter increases linearly with dopant concentration (x). The temperature dependence of thermopower measured for samples having different x revealed unusual increase in thermopower for the composition x = 0·5, for example, at 427°C, and the thermopower values for PbSe0·5 Te0·5, PbTe and PbSe were 292, 188 and 134 μV/K, respectively. A dramatic thermopower enhancement for PbSe0·5 Te0·5 is attributed to scattering of the majority charge carriers by the defect sites.